Understanding a Lovemark Brand Through the Sponsorship of the Peru National Football Team - Cruz-Donayre, Xiomara (2021)
Brands are eager to gain their consumers love and respect by connecting with them in a more efficient manner in order to become a Lovemark. This happens very frequently in the football “world” as it is the sport with the biggest audience in the planet. This study analyzes the Lovemark Axis inside the sponsorship strategies directed toward the female audience. Semi-structured interviews were conducted, with the aim of analyze the perception of the consumers exposed to the ads of the sponsor brands of the Peru national football team. Results evidenced that the love and respect elements for the sponsored brand contribute to the association of values and feelings of the sponsoring brand. These results support that although the construction of a Lovemark requires a great period of time, the use of sports sponsorship helps to generate greater visibility and association of the brand with the sport.